Real-Time Monitoring System for an Aquatic Surface Cleaning Robot using MIT App Inventor - Zabidi, Siti Farina Hidayah; Abdul Kadir, Herdawatie; Muhammad Danial (Evolution in Electrical and Electronic Engineering, 2021)
Nowadays, certain water resources in Malaysia have been polluted by garbage and also industrial trash due to the irresponsibility of some individuals and organizations. The polluted water has destroyed the aquatic ecosystem in the area. Normally, cleaning is done using big and bulky machines or using a manual operator to clean the water surface. The issue of cleaning with bulking machines, it will destroy and interrupt the existing ecosystem. For manual methods, sometimes it is dirty and dangerous. Even worse with the presence of sewage. Therefore, to overcome this problem, a portable surface cleaning robot is proposed. This device will help to clean the surface of the water and it also will be on a very wide controllable range. The Aquatic Surface Cleaning Robot is one of the initiatives to reduce the polluted water issue by cleaning unwanted foreign objects such as plastic products on the water surface. It will conduct activities such as removing algae, foreign objects and monitor water quality. In addition, the platform is embedded with a real-time vision monitoring system for better user interaction to control and longer range of control signals. Furthermore, it enhanced the overall design.